Mesoporous Hydroxyapatite/Chitosan Loaded With Recombinant-Human Amelogenin Could Enhance Antibacterial Effect and Promote Periodontal Regeneration - Liao, Yue; Li, Huxiao; Shu, Rong; Chen, Huiwen; Zhao, Liping; Song, Zhongchen; Zhou, Wei (Frontiers in Cellular and Infection Microbiology, 2020)
The recovery of impaired periodontium is still a challenge to the treatment of periodontitis. This study was the first to apply the mesoporous hydroxyapatites/chitosan (mHA/CS) composite scaffold to periodontal regeneration. The aim of our study is to evaluate the biological effects of mesoporous hydroxyapatite/chitosan (mHA/CS) loaded with recombinant human amelogenin (rhAm) on periodontal regeneration. The physicochemical properties of mHA/CS scaffolds were examined by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and Brunauer–Emmett–Teller (BET) analysis. Then, the biological effects of the mHA/CS loaded with rhAm were evaluated, including antibacterial effect, controlled-release capacity, osteogenic and cementogenic effects in vitro and in vivo. The antibacterial effect was tested on 1.5 mg/mL CS; 3 mg/mL mHA; 2.25 mg/mL mHA/CS; 4.5 mg/mL mHA/CS and 20 μg/mL rhAm. Tryptic Soy Broth culture medium was used as a baseline control. Osteogenic effect of rhAm (20 μg/mL rhAm), mHA/CS (4.5 mg/mL mHA/CS), and mHA/CS-rhAm (4.5 mg/mL mHA/CS and 20 μg/mL rhAm) on human periodontal ligament cells (hPDLCs) was evaluated in osteogenic media. The hPDLCs treated either with osteogenic media or Dulbecco's modified Eagle's medium (DMEM) alone were used as the baseline control. In the animal model, 4-week-old nude mice (BALB/c) (n = 6) implanted with root slices subcutaneously were used to observe the cementogenic effect in vivo. The root slices were treated with rhAm (20 μg/mL rhAm), mHA/CS (4.5 mg/mL mHA/CS), and mHA/CS-rhAm (4.5 mg/mL mHA/CS and 20 μg/mL rhAm). The root slices treated with osteogenic medium alone were used as the baseline control. The analyses showed that the mHA/CS particles were 2 μm in diameter and had a uniform pore size. The mesoporous structure was 7 nm in diameter and its surface area was 33.95 m2/g. The scaffold exhibited antibacterial effects against Fusobacterium nucleatum and Porphyromonas gingivalis. The mHA/CS scaffold sustainably released rhAm. The mHA/CS loaded with 20 μg/mL rhAm upregulated ALP activity, the expression levels of osteogenesis-related genes and proteins in vitro. Additionally, it promoted the formation of cementum-like tissue in vivo. Our findings suggest that mHA/CS loaded with 20 μg/mL rhAm could inhibit the growth of periodontal pathogens and promote the formation of bone and cementum-like tissue.